Motion-based remote control device for interaction with multimedia content - Rasteiro, Miguel António da Cunha (2016)
This dissertation describes the development and implementation of techniques to enhance the accuracy of low-complexity lters, making them suitable for remote control devices in consumer electronics. The evolution veri ed in the last years, on multimedia contents, available for consumers in Smart TVs and set-top-boxes, is not raising the expected interest from users, and one of the pointed reasons for this nding is the user interface. Although most current pointing devices rely on relative rotation increments, absolute orientation allows for a more intuitive use and interaction. This possibility is explored in this work as well as the interaction with multimedia contents through gestures. Classical accurate fusion algorithms are computationally intensive, therefore their implementation in low-energy consumption devices is a challenging task. To tackle this problem, a performance study was carried, comparing a relevant set of professional commercial of-the-shelf units, with the developed low-complexity lters in state-of-the-art Magnetic, Angular Rate, Gravity (MARG) sensors. Part of the performance evaluation tests are carried out under harsh conditions to observe the algorithms response in a nontrivial environment. The results demonstrate that the implementation of low-complexity lters using low-cost sensors, can provide an acceptable accuracy in comparison with the more complex units/ lters. These results pave the way for faster adoption of absolute orientation-based pointing devices in interactive multimedia applications, which includes hand-held, battery-operated devices.